State Aid Policies in Response to the COVID-19 Shock: Observations and Guiding Principles - Massimo Motta; Martin Peitz (Intereconomics)
Abstract As a general principle, state aid to firms and sector-specific support schemes should be used only when there are market failures; that is, when there are good reasons to believe that the market would not deliver efficient and/or equitable outcomes.